Pete the cat - Twinkle, twinkle, little star - Dean, James 1957- (Harper / HaperCollins, 2014)
Youngsters are invited to join Pete the Cat as he stars in the classic nighttime song "Twinkle, Twinkle, Little Star."
Keywords: Children's stories / Juvenile fiction; Nursery rhymes / Juvenile fiction; Cats / Juvenile fiction; Songs / Juvenile fiction; Cats; Children's stories; Nursery rhymes